Pola interaksi pendidik dan peserta didik pada abad 21 dalam perspektif pemikiran pendidikan Islam Al-Ghazali - Moh. Faizin; Amilatus Sholihah; Nova Puspita; Intan Cantika (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
Education is one of the interaction activities between educators and students in a learning activity. Interaction is a reciprocal relationship that influences each other between individuals and groups. Learning through interactions that are felt less harmonious can cause transmission gaps in a lesson. This is evidenced by some educators building bad relationships with their students such as being unfair, arrogant and choosing violence when solving a problem in the school environment. Al-Ghazali is an Islamic education figure who has focused on this problem since the 5th century H. The purpose of this study is to describe an interaction between educators and students. To achieve the objectives of a study, this research uses library research and documentary methods. This article aims to examine some of Al-Ghazali's theories about an educational interaction in a number of his studies on the topic of education. Al-Ghazali's concept can also be used as a reference for overcoming problems between educational interactions today